In vitro Evaluation of Oil Palm Fronds Fermented with Produren: A Durian Probiotic - Mardalena; Musnandar, E. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Increasing ruminant productivity requires a protein source not only from feed but also from rumen microbial activity. An increase in the activity of rumen microbes can be accomplished with arumen modifier, which is the role of produren (a durian probiotic). The current study aimed to determine the effect of produren on the in vitro fermentation of oil palm fronds in beef cattle rumen fluid. Methodology: The study used a completely randomized design with 4 treatments and4 replications. The treatments consisted of oil palm fronds without fermentation (NPF/control), oil palm fronds fermented with 2.5% produren (PF1), oil palm fronds fermented with 5% produren (PF2) and oil palm fronds fermented with 7.5% produren (PF3). The parameters measured were dry matter digestibility, organic matter digestibility, N-NH3, pH, the total volatile fatty acid (VFA) concentration and the acetic acid, propionic acid and butyric acid concentrations. The data were analyzed by Duncan’s multiple range test. Results: The oil palm fronds fermented with produren had a higher (p0.05) organic matter digestibility, pH or NH3 in the rumen fluid from beef cattle. Conclusion: Fermentation of oil palm fronds with produren at 7.5 g% DM improved dry matter digestibility and the total VFA concentration in the rumen fluid from beef cattle.